Maternal Mercury Exposure and Hypertensive Disorders of Pregnancy: A Systematic Review - Dantas, Aline de Oliveira; Castro, Thiania dos Santos da Silva de; Câmara, Volney de Magalhães; Santos, Aline de Souza Espindola; Asmus, Carmen Ildes Rodrigues Froes; Vianna, Angelica dos Santos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective The present review aimed to synthesize the evidence regarding mercury (Hg) exposure and hypertensive disorders of pregnancy (HDP).Data Sources The PubMed, BVS/LILACS, SciELO and UFRJ's Pantheon Digital Library databases were systematically searched through June 2021.Study Selection Observational analytical articles, written in English, Spanish, or Portuguese, without time restriction.Data Collection We followed the PICOS strategy, and the methodological quality was assessed using the Downs and Black checklist.Data Synthesis We retrieved 77 articles, of which 6 met the review criteria. They comprised 4,848 participants, of which 809 (16.7%) had HDP and 4,724 (97.4%) were environmentally exposed to Hg (fish consumption and dental amalgam). Mercury biomarkers evaluated were blood (four studies) and urine (two studies). Two studies found a positive association between Hg and HDP in the group with more exposure, and the other four did not present it. The quality assessment revealed three satisfactory and three good-rated studies (mean: 19.3 ± 1.6 out 28 points). The absence or no proper adjustment for negative confounding factor, such as fish consumption, was observed in five studies.Conclusion We retrieved only six studies, although Hg is a widespread toxic metal and pregnancy is a period of heightened susceptibility to environmental threats and cardiovascular risk. Overall, our review showed mixed results, with two studies reporting a positive association in the group with more exposure. However, due to the importance of the subject, additional studies are needed to elucidate the effects of Hg on HDP, with particular attention to adjusting negative confounding.
Keywords: mercury; pregnancy-induced hypertension; preeclampsia; eclampsia and gestational hypertension